End of the INF Treaty: Are We Entering a New Cold War Era? - Şafak OĞUZ; Mehmet Seyfettin EROL (Gazi Akademik Bakış)
This article analyzes possible consequences of the abolition of the Intermediate-Range Nuclear Forces (INF) Treaty, signed between the US and the USSR in 1987 and banning developing, testing and deploying intermediate-range missiles. The article argues that termination of the treaty would result in a conventional and especially a nuclear arms race as during the Cold War, and might trigger scrapping further agreements, although common sense in both parties enabled extending of the New START Treaty for 5 years. The new environment, with regional and global crises and massive armament by the global powers, including missile defense systems and hypersonic missiles, would endanger possible cooperation.